Search for large extra dimensions in dielectron and diphoton production. - Abbott, B; Abolins, M; Abramov, V; Acharya, B; Adams, D; Adams, M; Alves, G; Amos, N; Anderson, E; Baarmand, M; Babintsev, V; Babukhadia, L; et al. (2001)
We report a search for effects of large extra spatial dimensions in pp collisions at a center-of-mass energy of 1.8 TeV with the D0 detector, using events containing a pair of electrons or photons. The data are in good agreement with the expected background and do not exhibit evidence for large extra dimensions. We set the most restrictive lower limits to date, at the 95% C.L. on the effective Planck scale between 1.0 and 1.4 TeV for several formalisms and numbers of extra dimensions.